2020
DOI: 10.14393/bj-v36n0a2020-53563
|View full text |Cite
|
Sign up to set email alerts
|

Castor bean cake in top-dressing application as a source of nitrogen on the production and quality of zucchini organic seeds

Abstract: Studies in vegetables show that fertilization influences seed production positively, however, when the quality of the seeds is analyzed, the results are mostly inconsistent. The objective of this study was to evaluate the effect of castor bean cake (CBC) dose splitting in top-dressing application on the production and quality of zucchini organic seeds, as well as its effect on the macronutrient content of fruits and seeds. The experimental design was a randomized block design and four replications. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 13 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…According to Kano and coauthors [28], its accumulation in the seeds must occur only by absorption and transport during seed maturation, without redistribution of the senescent leaves to the seeds. Lanna and coauthors [29] observed that calcium was the least accumulated macronutrient in 'Caserta' zucchini seeds. However, its application resulted in a greater quantity of pollen grains per flower (Figure 1), which may favor greater seed production, mainly in manual pollinations used both in the production of seeds of some hybrids and in breeding [13,22].…”
Section: Resultsmentioning
confidence: 99%
“…According to Kano and coauthors [28], its accumulation in the seeds must occur only by absorption and transport during seed maturation, without redistribution of the senescent leaves to the seeds. Lanna and coauthors [29] observed that calcium was the least accumulated macronutrient in 'Caserta' zucchini seeds. However, its application resulted in a greater quantity of pollen grains per flower (Figure 1), which may favor greater seed production, mainly in manual pollinations used both in the production of seeds of some hybrids and in breeding [13,22].…”
Section: Resultsmentioning
confidence: 99%
“…italica), both with organic compost fertilization before planting and with S fertilization in top dressing. The organic matter also favors the increase of seed production of other horticultural crop species [4,11,12,13]. However, there are no reports for radish seed production about the importance of S and organic fertilization in seed production.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in organic fertilizers and research demonstrating gains in productivity and better soil characteristics with their use has increased in recent years [4,5,6,7,8]. However, most of this research has been done with fertilizer applied before planting, and researches about organic fertilizers in top dressing are scarce, but most of them has shown the importance of organic top dressing fertilization [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The supply of fertilizers at the right time is important to increase productivity and reduce nutrient losses. Due to the different requirements of nutrients amounts during the growth phases of plants and due to the rapid loss of nitrogen, mainly by leaching, it is important to split its application, to obtain greater production, using less fertilizer, making it possible to reduce costs [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation